PERAN PERBANKAN SYARI’AH DALAM PENGELOLAAN WAKAF UANG DI INDONESIA - Mohammad Aniq Kamaluddin (AL WASATH Jurnal Ilmu Hukum, 2020)
Waqf is known as a Muslim who has a finger shape that has an important role in the welfare of society. One form of endowment that has recently begun to be introduced in many parts of the Islamic world is the endowment of money. The practice of endowment of money that occurs in Islamic Countries uses the shari'ah bank as the manager of the endowment of that money. Likewise in Indonesia has issued a waqf law that allows waqf for movable objects consisting of money through Islamic financial institutions appointed by the Minister of Religion. The main problem in this research is the Role of the Sharia Bank in the Management of Money Waqf. In the publication of this journal, the author uses a library book, where the results of the literature review are taken from books, magazines, scientific works that are questioned with syariah banking and endowments, then the analysis writer uses descriptive analytic methods and content analysis. In this study, the authors found the role of Islamic banks is very necessary in the management of waqf money because the principle of waqf whose principal funds do not require much help the role of expert managers in this case the bank is the best alternative to manage social funds, has credibility and has associated with deposit insurance institutions .